1999
DOI: 10.1177/089686089901900106
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Causes of Discrepancy between Kt/V and Creatinine Clearance

Abstract: Objective This study examines the frequency of discrepancy between Kt/V urea and creatinine clearance (Ccr) measurements in patients on peritoneal dialysis (PD) and the reasons for this discrepancy. Design Nonrandomized, retrospective data analysis. Setting Single PD unit of a university teaching hospital. Patients All adult patients receiving PD at our center from January 1995 to December 1996. Methods Actual (a) and desired (d) body weight (BW) were used to calculate urea volume of distribution (V) and body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The physiological causes of these discrepancies are residual renal function and peritoneal solute transport type: Subjects with substantial residual renal function and adequate C pr N cr may be at risk for low K pr t/V ur ; those with low or even low-average transport and adequate K pr t/V ur may be at risk for low C pr N cr [8,10]. A preliminary report suggested that the discrepancy between the two clearances is more frequent, around 30%, when the recent weekly targets of 2.0 for K pr t/V ur and 60 liters for C pr N cr are tested [11].…”
mentioning
confidence: 99%
“…The physiological causes of these discrepancies are residual renal function and peritoneal solute transport type: Subjects with substantial residual renal function and adequate C pr N cr may be at risk for low K pr t/V ur ; those with low or even low-average transport and adequate K pr t/V ur may be at risk for low C pr N cr [8,10]. A preliminary report suggested that the discrepancy between the two clearances is more frequent, around 30%, when the recent weekly targets of 2.0 for K pr t/V ur and 60 liters for C pr N cr are tested [11].…”
mentioning
confidence: 99%
“…A previous retrospective study found that the results of Kt/V and Ccr dialysis were contradictory in nearly 23% of PD patients, and further analysis suggested that the reason may have been related to the role of renal filtration and reabsorption. 27 The creatinine produced during human metabolism is excreted mainly through glomerular filtration and renal tubular secretion, while urea can be partially reabsorbed by renal tubules after glomerular filtration, which causes a discrepancy in the statistical analysis results between assessments of Kt/V and Ccr.…”
Section: Discussionmentioning
confidence: 99%
“…However, hemodialysis-free weekend days are associated with increased fluid and electrolyte retention that likely increase the risk of cardiac death. An analysis of United States Renal Data System data revealed that 20.2% of cardiac deaths (vs 14.3% expected, P = .0005) occurred on Monday for patients undergoing hemodialysis on a Monday, Wednesday, and Friday schedule. Similar findings regarding the rates of cardiac death were observed on Tuesdays for patients undergoing hemodialysis on a Tuesday, Thursday, and Saturday schedule.…”
mentioning
confidence: 99%